METHODS FOR DETERMINING THE AMOUNT OF MULTIELECTRONIC SCINTILLATIONS ON THE SCREEN OF ELECTRO – OPTIC TRANSFORMER OF IMAGES - Zhekov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
One of the basic requirements when using electro – optical transformer (EOT) of images in space research is the low level of bright light flashes on the screen, called multi – electronic scintillations. The experimental research of number and brightness of scintillations show that the distribution of the multi–electronic scintillations’ number across the screen’s diameter could be approximated by a normal law. The analysis of multi – electronic scintillations amplitude spectrum shows, that in the center of the EOT’s screen, the number of scintillations with greater amplitude is significantly greater in comparison with those at the end of the active surface of the screen.